The Effect of The Snowball Throwing Learning Model on Students' Learning Outcomes in The Science Subject Of Grade IV - Rini Novianti Gultom; Osco Parmonganan Sijabat; Emelda Thessalonika (Jurnal Ilmu Sosial dan Humaniora, 2026)
This research aim for know The Effect of the Snowball Throwing Learning Model on Learning Outcomes Students in the Social Sciences Subject of Class IV of UPTD Sd Negeri 122299 Pematangsiantar. Study Design utilized is design experimental pre-test post-test group Because in design This there is test in pre- test form is given before treatment and post-test were given after treatment utilizing the model. Snowballing method Based on the discussion in this chapter, the reviewer explains the study output obtained along with the formulation of the problem and the proposed hypothesis, then all study activities are discussed regarding the impact of the teaching model. The application of the Snowballing method by the learning output of the science subject in Class IV UPTD SD N 122399 Pematang Siantar is as follows: Based on the study output by the subject in Class IV UPTD SD N 122399 Pematang Siantar, the average pre-test score in the science subject "Biodiversity" is 85.43 Not reaching the KKTP score of 70. The use of teaching tools by the natural science subject about snowball throwing, class IV, UPTD SD N 122399 Pematang Siantar, achieved an increase in learning output and an average post-test score of The figure reached 85.43, while the KKTP was 70. Based on the test output and data analysis, the hypothesis testing output in this study indicated a significant influence. The tested data showed a calculated T-value of 23.661. And the T table is 1.701, so the calculated T > T table, meaning that Ha is accepted and Ho is rejected. So it can be concluded that there is an influence by the teaching model. UPT DSDN 122399 Snowball Throwing by the Learning Output of Fourth Grade Students in Pematang Siantar.